Plasma wakefield acceleration experiments at FACET II. (12th January 2018) - Joshi, C; Adli, E; An, W; Clayton, C E; Corde, S; Gessner, S; Hogan, M J; Litos, M; Lu, W; Marsh, K A; Mori, W B; Vafaei-Najafabadi, N; et al.
Abstract: During the past two decades of research, the ultra-relativistic beam-driven plasma wakefield accelerator (PWFA) concept has achieved many significant milestones. These include the demonstration of ultra-high gradient acceleration of electrons over meter-scale plasma accelerator structures, efficient acceleration of a narrow energy spread electron bunch at high-gradients, positron acceleration using wakes in uniform plasmas and in hollow plasma channels, and demonstrating that highly nonlinear wakes in the 'blow-out regime' have the electric field structure necessary for preserving the emittance of the accelerating bunch. A new 10 GeV electron beam facility, Facilities for Accelerator Science and Experimental Test (FACET) II, is currently under construction at SLAC National Accelerator Laboratory for the next generation of PWFA research and development. The FACET II beams will enable the simultaneous demonstration of substantial energy gain of a small emittance electron bunch while demonstrating an efficient transfer of energy from the drive to the trailing bunch. In this paper we first describe the capabilities of the FACET II facility. We then describe a series of PWFA experiments supported by numerical and particle-in-cell simulations designed to demonstrate plasma wake generation where the drive beam is nearly depleted of its energy, high efficiency acceleration of the trailing bunch while doubling its energy and ultimately, quantifying the emittance growth in a single stage of a PWFA that has optimally designed matching sections. We then briefly discuss other FACET II plasma-based experiments including in situ positron generation and acceleration, and several schemes that are promising for generating sub-micron emittance bunches that will ultimately be needed for both an early application of a PWFA and for a plasma-based future linear collider.